Analysis and Simulation of Meshing Efficiency of Helical Gear Differential Gear Train - Zhou Chunguo; Bai Wenchao; Cui Yahui; Wang Huiwu (Jixie chuandong)
On the basis of taking 2K-H type helical differential gear train as the basic prototype,by analyzing the transmission efficiency of its transformation part and piecewise integration in meshing range,the result of the meshing efficiency of the internal and external contacted helical gears from the actual helical gears meshing is got. At the same time,the concept of the ideal machine is introduced,with the consideration of the axial overlap of the helical gear and the gear on the frictional engagement of the power loss,the formula of the helical gear differential gear train transmission efficiency is deduced. By using the given example numerical,theoretical value of the gear train efficiency is calculated,and this result is consist with the simulation result obtained by MATLAB and ADAMS software co-simulation calculation. The method can be used for calculating the efficiency of the other type helical differential gear train.